Implicit measures of teachers' attitudes and stereotypes, and their effects on teacher practice and student outcomes: A review. (April 2022) - Denessen, Eddie; Hornstra, Lisette; van den Bergh, Linda; Bijlstra, Gijsbert
Abstract: In this paper, research on implicitly measured teacher associations with social groups of students (attitudes and stereotypes) is reviewed. The aim of this review is to describe the theoretical and methodological underpinnings of the use of implicit measures in educational research, to summarize the research completed so far in which implicit measures have been used, how implicitly measured attitudes and stereotypes are related to different teacher factors and student outcomes, and to discuss challenges and directions for future research on implicit measures and their effects. A total of 49 studies was reviewed. These studies show that the use of implicit measures of teacher attitudes and stereotypes has great potential for the understanding of differential treatment of students by their teachers, but also that this line of research needs further development, with more focus on the validation of implicit measures and study designs in experimental and field settings. Highlights: 49 studies with implicit measures of teachers' group associations are reviewed. Implicit group associations relate to differential treatment of students by their teachers. Implicitly measured teacher attitudes were predictive of student outcomes. Implicit measures have a higher predictive value than explicit measures.